A4NH 2018 annual report highlights: Flagship 5 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2019)
This includes three highlights document for Flagship 5 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Examining the Link between African Rice Production and Malaria Highlight 2: Supporting Government Decisions and Planning on Rift Valley Fever Interventions Highlight 3: Improving Hospital Diagnostics for Human Brucellosis